Graphene Paste Electrode: Analytical Applications for the Quantification of Dopamine, Phenolic Compounds and Ethanol. Issue 8 (18th July 2014) - Gutierrez, Fabiana; Comba, Fausto N.; Gasnier, Aurélien; Gutierrez, Alejandro; Galicia, Laura; Parrado, Concepción; Rubianes, María D.; Rivas, Gustavo A.
Abstract This work reports the analytical applications of a graphene paste electrode (GrPE) for the quantification of dopamine, ethanol and phenolic compounds. Dopamine was detected by differential pulse voltammetry‐adsorptive stripping with medium exchange at submicromolar levels even in the presence of high excess of ascorbic acid and serotonin. The electrocatalytic activity of graphene towards the oxidation of NADH and the reduction of quinones allowed the sensitive amperometric determination of ethanol and phenols using GrPE modified with alcohol dehydrogenase/NAD+ or polyphenol oxidase, respectively, with successful applications in real samples like alcoholic beverages and tea.